Producing 100+ MPa Field Concrete in Developing Countries: Requirements and Challenges - Youssef ElHawary; Mohamed Hamdy; John Haroun; Omar Youssef; Tamer Breakah; Mohamed Nagib (Journal of Building Materials and Structures)
Over the past three decades, there has been a paradigm shift in the concrete industry in which high strength and high performance concrete became more widely in use. However, producing ultra-high strength concrete surpassing 100 MPa compressive strength in the field remains a challenging task. This is primarily due to the various factors involved in such concrete and its sensitivity to many of these factors. This study aims at producing field concrete surpassing 100 MPa compressive strength using readily available materials worldwide. The study also addresses the requirements and challenges of 100+ MPa concrete in the field in order to possess similar properties to conjugate mixtures produced in the laboratory having same mix proportions. Concrete mixtures were prepared with different water-to-cement ratios and incorporated variety of chemical and mineral admixtures. Tests included fresh concrete, self-consolidation as well as hardened concrete properties in order to determine the properties of the concrete produced. The impact of other vital factors such as mixing process, ambient temperature, curing process and pumping are addressed taking field conditions into consideration. Several field visits were conducted to monitor field concrete that was produced using the designated mixtures. The study herein revealed that reaching 100 plus MPa concrete is doable using variety of readily-available constituents and mix proportion. However, the study pinpoints the importance of other crucial factors and field practices. Recommendations are provided to concrete users and practitioners to exercise better quality control and ensure high rate of success in producing ultra-high strength concrete in the field.